Metabolic profile of human coelomic fluid. (January 2017) - Virgiliou, C; Valianou, L; Witting, M; Moritz, F; Fotakis, C; Zoumpoulakis, P; Chatziioannou, A C; Lazaros, L; Makrydimas, G; Chatzimeletiou, K; Raikos, N; Theodoridis, GA
Aim: Till now there is very limited knowledge on the molecular content of coelomic fluid and cells. This study presents the first attempt to elucidate the metabolic profile of such samples.Methodology: Samples were collected via coelocentesis from 41 women during the first trimester of gestation. Metabolic content was assessed using four different analytical platforms. For targeted analysis a hydrophilic interaction chromatography ultra high performance LC–MS/MS method was applied. Holistic analysis performed by GC–MS, NMR spectroscopy and ion cyclotron ultra-high resolution MS (FT–ICR–MS) instrumentation.Results & Conclusions: Our observations suggest coelomic fluid and cells as promising biosamples, rich in metabolites with potential use in mammalian system biology studies.